Publicly Declared Positions In The Context Of TheKarabakh Process: Problems Of Consistency And Continuity - Mkhitarian, Karine (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
The paper focuses on the analysis of the publicly declared positions of Nikol Pashinian, the Prime Minister of Armenia, in the context of the Karabakh process, examining the impact of the declared position on the negotiation process and identifying the shifts in the leader’s positions on the Karabakh issue over the time. The research is conducted using the qualitative content analysis method. The research demonstrates that Pashinian’s declared positions on Karabakh issues led to the disruption of the negotiation process and identifies that the leader’s declared positions were targeted at preserving public support and staying in power have changed over time due to the changing circumstances.
Keywords: Political science